2023
DOI: 10.57041/pjs.v75i1.829
|View full text |Cite
|
Sign up to set email alerts
|

Working Principle and Intelligence of Smart Infusion Pump

Abstract: There is a tremendous demand on the critical care resources due to the extensivespread of the ongoing coronavirus pandemic and the large number of patients requiring critical care.The efficacy of a device directly influences how long a patient lives since patients are often receivingcritical care. Smart infusion pump is a medical device that can drip fluids into the patient's body. Thisdevice is considered as one of the most safety-critical medical devices due to the way it functions andthe risks it presents. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In addition, GA has a low viscosity with high emulsification properties and strong stability, which can be used as an excellent film-forming material in food and non-food applications, e.g., bakery, beverages, fruits and vegetables, pharmaceuticals, and cosmetics (Kawhena et al, 2021;Taher et al, 2022). The effects of GA as an edible coating on the quality and shelf life of tomato (Ali et al, 2013), summer squash (Bleoanca et al, 2022), plum (Fawole et al, 2020), pomegranate (Kawhena et al, 2021), kaki (Saleem et al, 2023), peach (Taher et al, 2022), apple (Soppelsa et al, 2023), acid lime (Beheiry et al, 2023), strawberries (De Bruno et al, 2023), guava (El-Gioushy et al, 2022), banana (Maqbool et al, 2011), and papaya (Maqbool et al, 2011) have been investigated. The findings of the previous studies revealed that coating with GA delayed the ripening, decreased weight loss, reduced shrivel, postponed microbial spoilage, preserved the antioxidants, lowered browning and chilling damage, and prolonged the shelf life of fruits during storage.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, GA has a low viscosity with high emulsification properties and strong stability, which can be used as an excellent film-forming material in food and non-food applications, e.g., bakery, beverages, fruits and vegetables, pharmaceuticals, and cosmetics (Kawhena et al, 2021;Taher et al, 2022). The effects of GA as an edible coating on the quality and shelf life of tomato (Ali et al, 2013), summer squash (Bleoanca et al, 2022), plum (Fawole et al, 2020), pomegranate (Kawhena et al, 2021), kaki (Saleem et al, 2023), peach (Taher et al, 2022), apple (Soppelsa et al, 2023), acid lime (Beheiry et al, 2023), strawberries (De Bruno et al, 2023), guava (El-Gioushy et al, 2022), banana (Maqbool et al, 2011), and papaya (Maqbool et al, 2011) have been investigated. The findings of the previous studies revealed that coating with GA delayed the ripening, decreased weight loss, reduced shrivel, postponed microbial spoilage, preserved the antioxidants, lowered browning and chilling damage, and prolonged the shelf life of fruits during storage.…”
Section: Introductionmentioning
confidence: 99%